2013
DOI: 10.5012/jkcs.2013.57.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Hydroalumination Reaction of Cyclopropane with Alane

Abstract: ABSTRACT. The hydroalumination of cyclopropane has been investigated using the B3LYP density functional method employing several split-valence basis sets. It is shown that the reaction proceeds via an intermediate weakly bound complex and a four-centered transition state. Calculations at higher levels of theory were also performed at the geometries optimized at the B3LYP level, but only slight changes in the barriers were observed. Structural parameters for the transition state are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Cyclopropane is known to undergoe addition reactions, 4 and computational studies on the hydroboration and hydroalumination 5,6 of cyclopropane have been reported from this. 5 To our knowledge there have been no reports of theoretical studies of the reaction of cyclopropane with MgH 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Cyclopropane is known to undergoe addition reactions, 4 and computational studies on the hydroboration and hydroalumination 5,6 of cyclopropane have been reported from this. 5 To our knowledge there have been no reports of theoretical studies of the reaction of cyclopropane with MgH 2 .…”
Section: Introductionmentioning
confidence: 99%